The Dynamics of Long Terminal Repeat Retrotransposon Proliferation and Decay Drive the Evolution of Genome Size Variation in Capsicum - Qian Liu; Pinbo Liu; Shenghui Wang; Jian Yang; Liangying Dai; Jingyuan Zheng; Yunsheng Wang (Plants, 2025)
Capsicum (pepper) is an economically vital genus in the Solanaceae family, with most species possessing about 3 Gb genomes. However, the recently sequenced Capsicum rhomboideum (~1.7 Gb) represents the first reported case of an extremely compact genome in Capsicum, providing a unique and ideal model for studying genome size evolution. To elucidate the mechanisms driving this variation, we performed comparative genomic analyses between the compact Capsicum rhomboideum and the reference Capsicum annuum cv. CM334 (~2.9 Gb). Although their genome size differences initially suggested whole-genome duplication (WGD) as a potential driver, both species shared two ancient WGD events with identical timing, predating their divergence and thus ruling out WGD as a direct contributor to their size difference. Instead, transposable elements (TEs), particularly long terminal repeat retrotransposons (LTR-RTs), emerged as the dominant force shaping genome size variation. Genome size strongly correlated with LTR-RT abundance, and multiple LTR-RT burst events aligned with major phases of genome expansion. Notably, the integrity and transcriptional activity of LTR-RTs decline over evolutionary time; older insertions exhibit greater structural degradation and reduced activity, reflecting their dynamic nature. This study systematically delineated the evolutionary trajectory of LTR-RTs—from insertion and proliferation to decay–uncovering their pivotal role in driving Capsicum genome size evolution. Our findings advance the understanding of plant genome dynamics and provide a framework for studying genome size variation across diverse plant lineages.